2003
DOI: 10.1128/jcm.41.6.2522-2529.2003
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Treponema phagedenis -Like Spirochetes Isolated from Papillomatous Digital Dermatitis Lesions in Dairy Cattle

Abstract: Four spirochete strains were isolated from papillomatous digital dermatitis (PDD) lesions in Iowa dairy cattle and compared with two previously described spirochete strains isolated from dairy cattle in California. These six strains shared an identical 16S ribosomal DNA sequence that was 98% similar to Treponema phagedenis and 99% similar to the uncultivated PDD spirochete sequence DDLK-4. The whole-cell protein profiles resolved by sodium dodecyl sulfate-polyacrylamide gel electrophoresis of these six strains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
91
2
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(99 citation statements)
references
References 38 publications
5
91
2
1
Order By: Relevance
“…This indicated the presence of two (or, most commonly, three) phylogroups in BDD lesions. Isolation data from previous studies suggested that the group 2 isolates (T. phagedenis-like) might be the only phylogroup specifically associated with BDD, as they have been the most commonly isolated ones (13,32,33). The current data clearly refute this premise, as the new PCR tests indicated the presence of group 2 treponemes in nearly all BDD lesions (98%) and detected group 1 treponemes (T. medium/T.…”
Section: Discussioncontrasting
confidence: 40%
“…This indicated the presence of two (or, most commonly, three) phylogroups in BDD lesions. Isolation data from previous studies suggested that the group 2 isolates (T. phagedenis-like) might be the only phylogroup specifically associated with BDD, as they have been the most commonly isolated ones (13,32,33). The current data clearly refute this premise, as the new PCR tests indicated the presence of group 2 treponemes in nearly all BDD lesions (98%) and detected group 1 treponemes (T. medium/T.…”
Section: Discussioncontrasting
confidence: 40%
“…Still, the high number of invasive spirochetes observed suggests an active contribution of this group to DD pathogenesis (8,9,12,16,24,35). This hypothesis is further substantiated by the fact that serum samples from cattle infected with DD contain elevated levels of antibody to Treponema antigens (13,25,36). Also, it has been demonstrated that four Treponema strains previously isolated from DD-infected cows were able to induce abscess formation in mice (18).…”
supporting
confidence: 49%
“…We identified a number of environmental microbes expressing proteins that contain peptide sequences with high homology to the R3 core region of B:11-23 R22E peptide (ALYLVCGEE). These microbes included species that are commonly isolated from poultry or dairy animals and environmental microbes that are commonly encountered (23)(24)(25)(26). DQ8-restricted insulin-specific T-cell clones were activated by these homologous microbial peptides as effectively as the B:11-23 R22E peptide.…”
Section: Discussionmentioning
confidence: 99%
“…We identified four microbial peptides with high-sequence homology to ALYLVCGEE (Table S3). These sequences were derived from Bacteroides salanitronis, a common inhabitant of chicken intestine/cecum (23), Clostridium acetobutylicum, a soil dwelling Clostridium species (24), Treponema phagedenis, a pathogen of papillomatous digital dermatitis isolated from Iowa dairy cattle (25), and Microscilla marina, a bacterial group frequently found on marine particulates (26). All of the T-cell clones tested responded to stimulation with these bacterial peptides and the responses, as evaluated by the stimulation index, were of comparable magnitude to the modified B:11-23 R22E peptide (Fig.…”
Section: Insulin-reactive T-cell Clones Respond To the Microbially Dementioning
confidence: 99%